THE DIAGNOSTIC MARKERS’ APPLICATION OF THE ORAL LIQUID IN THE EARLY DIAGNOSTICS OF THE DENTAL MOBIDITY IN THE STAFF OF THE STEEL-MANUFACTURING ENTERPRISES’ EMPLOYEES - A.V. Samoilenko; S.V. Pavlov; I.V. Vozna (Український стоматологічний альманах, 2018)
The dental health of the industrial enterprises’ workers has specific differences from the average indicators of the epidemiological examinations, which is associated with a negative effect on the tissue and oral cavity of the working zone’s atmosphere. Under prolonged exposure of the low concentrations of harmful substances, i.e, due to the chronic intoxication in the oral cavity can occur as a disease of the mucous membrane, as well as the disease of hard tissues of the teeth. Despite the presence of measures on the occupational safety and accident prevention protection, the industrial environment of the enterprises is an extreme condition for workers, which requires the further development of effective comprehensive methods of the prevention and the treatment of the major dental diseases.